The Application of Contextual Teaching and Learning Approach toward Students in MTs Muhammadiyah 31 Lamongan on Scientific Writing - M. Suhad (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2020)
The scientific writing skills of students in ninth class of MTs Muhammadiyah 31 Cumpleng Brondong Lamongan are still low and need to be improved. This study aims to describe the application of contextual teaching and learning to Junior high school students in scientific writing. This research is a classroom action research that consists of 2 cycles. The subject of this research is students students in ninth class of MTs Muhammadiyah 31 Cumpleng. Data was collected using test, observation and interview. The data from the test results were analyzed using descriptive statistics, while data obtained by from observations, and interviews were described narratively. The results showed that the contextual teaching and learning approach was very effective in improving the scientific writing skills of ninth class students of MTs Muhammadiyah 31 Cumpleng and the average score was 62.13, in the first cycle and the results increased again in the second cycle, 77.15.